Organizational justice and insomnia: Relationships between justice components and insomnia symptoms among private company workers in Japan. Issue 2 (25th April 2015) - Hayashi, Toshio; Odagiri, Yuko; Takamiya, Tomoko; Ohya, Yumiko; Inoue, Shigeru
Abstract : Organizational justice and insomnia: Relationships between justice components and insomnia symptoms among private company workers in Japan: Toshio Hayashi, et al . Department of Preventive Medicine and Public Health, Tokyo Medical University Objective: Organizational justice (OJ) is an important psychosocial factor and it consists of several components. Previous studies have shown that low perceived OJ is associated with various health problems. However, the relationships between each justice component and health outcomes have not been fully examined. The purpose of this study was to clarify the relationships between OJ and insomnia, including OJ components and insomnia symptoms. Methods: Cross‐sectional self‐reported questionnaire data from 1, 893 employees (92.2% of subjects) were collected. OJ was measured using the Japanese version of the OJ questionnaire, which has four components (distributive, procedural, interpersonal and informational). Insomnia was assessed with the Athens Insomnia Scale. Logistic regression analysis, with insomnia as a dependent variable and OJ as an independent variable, was conducted. Results: Subjects with low overall OJ had a higher risk of insomnia (adjusted odds ratio (AOR), 2.37; 95% confidence interval (CI), 1.59 to 3.53) and two insomnia symptoms (AOR of 2.47 and 95% CI of 1.68 to 3.65 for sleep induction problem; AOR of 1.73 and 95% CI of 1.21 to 2.48 for sleep maintenance problem). The four justice components were all associated with insomnia and sleep induction problems. Sleep maintenance problems were associated with only the distributive justice component. Conclusions: All four justice components were associated with both insomnia and sleep induction problems. Sleep maintenance problems, however, showed different features. Specifically, the distributive justice component seemed to be a key factor in the relationship between OJ and insomnia. These findings might provide useful information for preventing the adverse effects of insomnia.